Strong field tests of gravity with PSR J1141-6545 - Krishnan, V.; Van Straten, W.; Rosado, P.; Bailes, M.; Keane, E.; Bhat, Ramesh; Flynn, C. (2017)
The initial results from timing observations of PSR J1141-6545, a relativistic pulsar-white dwarf binary system, are presented. Predictions from the timing baseline hint at the most stringent test of gravity by an asymmetric binary yet. The timing precision has been hindered by the dramatic variations of the pulse profile due to geodetic precession, a pulsar glitch and red timing noise. Methods to overcome such timing irregularities are briefly presented along with preliminary results from the test of the General Theory of Relativity (GR) from this pulsar.